KAJIAN MACAM PUPUK KANDANG TERHADAP INTENSITAS KERUSAKAN HAMA BELALANG KEMBARA (LOCUSTA MIGRATORIA MANILENSIS L.) PADA 3 (TIGA) JENIS JAGUNG (ZEA MAYS SSP. MAYS) - Rohman, Amin Fathul; Santosa, Sartono Joko; Siswadi, Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
The research about study Kind Of Animal Manures To The Intensity Of Locust Pest Damage ( Locusta Migratoria Manilensis L. ) on three Types Of Corn Plants (Zea mays ssp. mays), with aim to test Kind Of Animal Manures To The Intensity Of Locust Pest Damage ( Locusta Migratoria Manilensis L. ) on three Types Of Corn Plants (Zea mays ssp. mays) had been done from 4 November 2019 to 17 January 2020, in Siderejo hamlet, Sajen Village, Trucuk District, Klaten Regency, Central Java, with elevation in 130m above sea level and regosol soil type. This research used a factorial Randomized Completion Block Design (RCBD) with method arranged split plot or separate tile layout design consist of two factors treatment with twelve combinations treatment and each treatment three replication. The parameters observed: attack symptoms, attack intensity, number of cobs, length of cobs, weight of fresh cobs per-plant, and weight of fresh cobs per-plot. The result of the research indicate that: (1) the most even intensity of attacks due to locust pest is found in the type of black corn, symptoms of locust attacks begin to appear at 10 days after planting on black corn. (2) The intesnsity attack of the locust pest influential attack on (V2P3) namely the treatment of chicken manure with a dose per plot of 608g on the type of white corn that is equal to 25,01. (3) The treatment of chicken manure and the type of white corn effect on the number of corn cobs gives the highest average value 1,33 and the length of the cob with the average value of 20,75.